2015
DOI: 10.1007/s00024-015-1033-x
|View full text |Cite
|
Sign up to set email alerts
|

Mining-Induced Stress Transfer and Its Relation to a $$\text{M}_w$$ M w  1.9 Seismic Event in an Ultra-deep South African Gold Mine

Abstract: On 27 December 2007 a M w 1.9 seismic event occurred within a dyke in the deep level Mponeng gold mine, South Africa. From the seismological network of the mine and the one from the JAGUARS group, the hypocentral depth (3509 m), focal mechanism and aftershock location was estimated. Since no mining activity took place in the days before the event, dynamic triggering due to blasting can be ruled out as the cause. To investigate the hypothesis that stress transfer, due to excavation of the gold reef, induced the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…The stress changes owing to the approaching mining front on the PG dyke are modeled by Ziegler [77]. A main shock with magnitude of M W = 1.9 occurred on 27 December 2007 in the center of the AE monitoring network [33,36,74].…”
Section: Gold Mine Mponeng In South Africamentioning
confidence: 99%
See 3 more Smart Citations
“…The stress changes owing to the approaching mining front on the PG dyke are modeled by Ziegler [77]. A main shock with magnitude of M W = 1.9 occurred on 27 December 2007 in the center of the AE monitoring network [33,36,74].…”
Section: Gold Mine Mponeng In South Africamentioning
confidence: 99%
“…Yabe et al [77] showed that the aftershock AE events clearly delineated a plane in the PG dike with a strike of N22W and a dip of 68° toward N68E (Figure 17). Because waveforms of the main shock recorded by the AE network were saturated in AE recordings, the main shock was analyzed using waveform data of the in-mine geophone network.…”
Section: Gold Mine Mponeng In South Africamentioning
confidence: 99%
See 2 more Smart Citations
“…The stress field also provides critical a priori information for safe and sustainable underground engineering such as wellbore planning and stability, reservoir management, tunnelling, mining, and underground waste storage (Altmann et al, 2014;Cornet et al, 1997;Fuchs and Müller, 2001;Moeck and Backers, 2011;Tingay et al, 2008;Zang et al, 2013;Ziegler et al, 2015;Zoback, 2010). The quantification of the criticality of the in situ stress state in terms of fault reactivation in advance of any underground treatment is essential for identifying areas of low criticality for safe and efficient utilization of the subsurface (Hornbach et al, M. O. Ziegler et al: Multi-stage 3-D stress modelling 2015; Zoback et al, 1985;Häring et al, 2008;Kohl and Mégel, 2007).…”
Section: Introductionmentioning
confidence: 99%